2007
DOI: 10.1002/chem.200700254
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Rational Design of Ruthenium CO2 Hydrogenation Catalysts by Ab Initio Metadynamics

Abstract: Complete reaction pathways relevant to CO2 hydrogenation by using a homogeneous ruthenium dihydride catalyst ([Ru(dmpe)2H2], dmpe=Me2PCH2CH2PMe2) have been investigated by ab initio metadynamics. This approach has allowed reaction intermediates to be identified and free‐energy profiles to be calculated, which provide new insights into the experimentally observed reaction pathway. Our simulations indicate that CO2 insertion, which leads to the formation of formate complexes, proceeds by a concerted insertion me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 63 publications
3
57
0
Order By: Relevance
“…[27] Field and co-workers reported that the trans isomer also exists at a ratio of cis:trans = 12:1 at 240 K in toluene. [28] We also confirmed the minor presence of the trans isomer based on 31 P and 1 H NMR data (quintet at d = À10.3 ppm in 1 H and d = 49.0 ppm in 31 P, see Supporting Information and reference [28]) and their 2D correlation. We obtained a ratio of cis:trans = 18:1 at 300 K in toluene.…”
Section: A C H T U N G T R E N N U N G (Ocho) 2 ] and Trans-[ru-a C Hsupporting
confidence: 81%
See 3 more Smart Citations
“…[27] Field and co-workers reported that the trans isomer also exists at a ratio of cis:trans = 12:1 at 240 K in toluene. [28] We also confirmed the minor presence of the trans isomer based on 31 P and 1 H NMR data (quintet at d = À10.3 ppm in 1 H and d = 49.0 ppm in 31 P, see Supporting Information and reference [28]) and their 2D correlation. We obtained a ratio of cis:trans = 18:1 at 300 K in toluene.…”
Section: A C H T U N G T R E N N U N G (Ocho) 2 ] and Trans-[ru-a C Hsupporting
confidence: 81%
“…[31] The Ru À H bond of TS 2-3 is elongated to 2.30 and the Ru···O distance is 2.92 . Interestingly, the formate unit of TS 2-3 undergoing rotational movement has nearly the same bond lengths and angles as the formate ion COOH ) to give 4, in which the formate hydrogen atom points away from the Ru center and the formate oxygen atom is in the vicinity of the methyl hydrogen atoms of the dmpe ligand.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…295,299 Simulations indicate that CO 2 insertion, which leads to the formation of formate complexes, is a rapid process with a relatively low activation barrier. 299 The activation energy of the H 2 insertion step is lower for the trans isomer than that for the cis isomer. 299 Complex cis-(PMe 3 ) 4 RuCl(OAc) (1, OAc is acetate) has performed favorable activity for CO 2 hydrogenation as shown in Table 4.…”
Section: Mechanistic Understandingmentioning
confidence: 99%